A CASE FOR THE NORTH CAUCASUS MILITARY SURVEY STUDYING (BASED ON THE ELBRUS EXPEDITION OF THE GENERAL G. A. EMANUEL) - T. A. Kolosovskaya (Гуманитарные и юридические исследования)
The article studies the history of a survey carried out at the Elbrus site, initiated by the Russian military department in 1829. The author analyses the reasons for setting the expedition, its essence, conditions and results, based on the official reports and published participants' evidences. The author infers that the site survey taken by some scientists and surveyors accompanied by the military troops turned into a specific form of a military survey studying the North Caucasus during the Caucasus War epoch.